Pengembangan dan Uji Kinerja Sistem Siber Fisik Refrigerasi Pada Kapal Ikan: Optimizing Fisheries Operations through Real-Time Monitoring and Cyber-Physical System Integration - Suhengki, Gemma Cahya Hafifah Suhengki; Jaya, Indra; Manik, Henry Munandar (PERTETA, 2024)
The rapid advancement of technology in the contemporary era has inspired individuals to contemplate more efficient and appropriate technologies, that potentially offer substantial benefits for many applications. Among these progressive technologies are the Internet of Things (IoT) and Cyber-Physical Systems (CPS). This research aims to develop a cyber-physical system for the supervision and regulation of refrigeration systems for fishing vessels via smartphones. This approach is seamlessly integrated into the fishing industry to enhance operational efficiency and optimize the preservation of fishery products. We have successfully applied IoT and CPS technologies for effective monitoring and control of the refrigeration system. In evaluating the accuracy of this application, two sensors were employed for analysis, specifically the primary temperature sensor and the reference temperature sensor. The principal yardstick for assessing measurement accuracy in this research is the standard deviation in sensor readings. The research findings reveal that the measured data from the primary temperature sensor and reference temperature sensor demonstrates a minimal standard deviation, signifying a high level of measurement precision. The expected outcome of implementing this system is the capability to regulate and monitor the refrigeration system, thus enabling fishermen to minimize losses in the fishery production process and elevate the quality of fishery products.